2021
DOI: 10.3390/v13122354
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in the Epidemiology of COVID-19: The Croatian ‘One Health’ Perspective

Abstract: During the four pandemic waves, a total of 560,504 cases and 10,178 deaths due to COVID-19 were reported in Croatia. The Alpha variant, dominant from March 2021 (>50% of positive samples), was rapidly replaced by Delta variants (>90%) by August 2021. Several seroprevalence studies were conducted in different populations (general population, children/adolescents, professional athletes, healthcare workers, veterinarians) and in immunocompromised patients (hemodialysis patients, liver/kidney transplant reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…However, there is the wide variety of pathogens that may transfer between humans and dogs, posing health risks to both ( 6 ). The benefits of dog ownership must therefore be weighed with the possible zoonotic disease implications that may be associated with these relationships ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is the wide variety of pathogens that may transfer between humans and dogs, posing health risks to both ( 6 ). The benefits of dog ownership must therefore be weighed with the possible zoonotic disease implications that may be associated with these relationships ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the appearance of the Alpha variant (Phylogenetic Assignment of Named Global Outbreak (PANGO) lineage B.1.1.7) [ 18 , 19 , 20 ] in the population in February 2021 announced the beginning of the third epidemic wave, while the presence of the Delta variant (PANGO lineage B.1.617.2) [ 18 , 19 , 20 ] in June 2021 led to the fourth epidemic wave. Until the end of August 2021, the Delta variant with its sub-lineages [ 18 , 19 , 20 ] constituted more than 98% of all SARS-CoV-2 positive samples, while the Beta and Gamma variants were detected sporadically and connected with travellers to areas with a high prevalence and their contacts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, declining numbers of tested and confirmed COVID-19 cases were observed, which can be attributed to the epidemiological situation in Croatia characterized with declining incidence and prevalence of COVID-19[ 4 , 10 ]. The main strength of this in-field evaluation is the sample size, whereas the limitations include various swab-takers and six RAT operators/interpreters; however, they were always competent and well-educated personnel ( e.g., laboratory personnel or medical doctors).…”
Section: Discussionmentioning
confidence: 99%
“…The national recommendation that negative RAT results in symptomatic patients suggestive of COVID-19 should be further tested by RT-PCR seems like a good solution because negative RAT results do not rule out the infection, especially in the high prevalence settings during study period[ 4 ]. Identifying and confirming COVID-19 in symptomatic persons is important to provide appropriate care and implement public health measures without delay[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation